Communication and comprehension. Methodological rigor and civic engagement in Lucia Lumbelli’s research - Cardarello, Roberta; Bardulla, Enver (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
The article presents the impressive research work of the recently deceased Lucia Lumbelli, founding partner of SIRD. She was a very original researcher in topics such as the verbal communication in education, audiovisual communication and the promotion of text comprehension. The common ground of her research was always the aim to promote the students’ autonomy and motivation, which is often lacking because of sociocultural factors. Her pedagogical assumptions and research methodology, a kind of exploratory research, in which theoretical devices and empirical data interact, are also presented.